Pembentukan Kare (Kader Remaja) Peduli HIV dan Aids di Kalintung Temon Kulon Progo - Kurniawati, Herlin Fitriana; Rohmah, Fatiyatur (Universitas Respati Yogyakarta, 2019)
Based on PKBI data from Kulon Progo Regency, it is found that HIV-AIDS cases in Kulon Progo Regency experienced an increasing trend. There are many cases found of HIV-AIDS virus sufferers which spread in all sub-districts in this regency. Meanwhile, one of programs from the government is by doing health promotion toward people. The infection of HIV-AIDS in Kulon Progo is increasing based on the data. The rate of HIVinfected in 2016 touches 161 cases and of AIDS are 57 cases. The aim of this societal volunteering is the establishment of 10 youth cadres who concern with HIV-AIDS in Kalintung village, sub-district of Temon, Kulon Progo Regency, Yogyakarta, which are able to provide information about HIV-AIDS. The problem occurs in this study is that Siwates sub-village as part of Kaligintung village which is located in the Temon sub-district does not have reproductive health cadres, especially cadres of HIV-AIDS, there is no place to discuss reproductive health and HIV-AIDS, has never received information and has never attended training related to HIV-AIDS, there is still a low level of knowledge of youth about HIV, and the worse that there are 5 teenagers who have done premarital sex who have the potential infection to HIV-AIDS and the risk of unwanted pregnancies. The results and the outcomes produced are the formation of 10 youth cadres who concern with HIV-AIDS in Kalintung Temon Kulon Progo Yogyakarta who are able toÂ provide information on definitions, factors, efforts to prevent HIV-AIDS, the availability of HIV-AIDS modules as a handbook for cadres in serving health counseling.Keywords: HIV-AIDS, Youth, Cadres